Co-Firing Sistem Fludized Bed Berbahan Bakar Batubara dan Ampas Tebu - Suprapta Winaya, I Nyoman; Darma Susila, Ida Bagus Agung (Jurnal Energi Dan Manufaktur; Vol 4, No.2 Oktober 2010, 2012)
Utilization of biomass energy resources as a source of alternative energy in Indonesia is very potential, bagasse is one suchexample. Baggase fuel can becombined with other fossil energy such as coal called Co-firing process to increase its calorificvalue and reduce green house gas emission. Research was conduted on the unit of fludized bed combustion (FBC) laboratoryscale of 50 mm in diameter and 100 mm in height. In this study, an external heating temperature (500 oC and 600 oC) with airsuperficial velocity (Uo) is varied which is 5 cm/s , 9 cm/s,and 13 cm/s. After the reactor reached operating temperature,fluidization air exhaled from below the distributor plate, and pellet fuel bagasse and coal mixture was inserted so that thecombustion occured. The temperature changes and gas emissions generated during the combustion process were analyzed.Based on the investigation, a complete combustion was occurred at velocity of 5 cm/s with operation temperature of 600 oC
Keywords: fluidized bed combustion, bagasse, gas emissions, volatile substances